Light and Scanning Observations on a Denticula species reported from South Africa and endemism of the diatom genus Tetralunata (Rhopalodiales, Bacillariophyceae) - Kociolek, J. Patrick; Greenwood, Megan; Rogers, Dillan; Hamsher, Sarah E.; Miller, Scott; Li, Jingchun; Chang, Aimee Caye G.; Taylor, Jonathan (Phytotaxa, 2024)
Denticula costata Hustedt was originally described from fossil material from Sumatra and later assigned to the genus Tetralunata. Although Tetralunata was thought to be endemic to Indonesia, D. costata has been reported from wetwalls from South Africa. This disparity in locality prompted us to investigate the D. costata in South Africa further. D. costata (now T. costata) specimens and the species reported from South Africa were different in size, shape, and structure of the raphe system. These differences, as well as comparisons to other Denticula species, allowed us to determine that the South African specimens have not been described previously. Valve ultrastructure, including the canal raphe, areolae with volate occlusions, and presence/structure of the septa suggest this new species belongs to the genus Tetralunata. This is the first report of Tetralunata from outside of Indonesia. Herein, we describe Tetraluanata schoemanii sp. nov. and its systematic placement close to, but separate from, Epithemia. This first report of Tetralunata from outside of Indonesia, increases our understanding of the genus range and displays a unique biogeographical pattern that warrants further investigation in the future.